The depressive situation - Jacobs, Kerrin A. (Frontiers in Psychology, 2013)
From a naturalistic perspective on mental illness, depression is often described in terms of biological dysfunctions, while a normative perspective emphasises the lived experience of depression as a harmful condition. The paper relates a conceptual analysis of ‘depressive situation’ to an analysis of the lived experience of depression. As such, it predominantly aims to specify depression as a harmful condition in lights of normative perspective on mental disorder, but partially refers to empirical research, i.e. naturalistic perspective on depression, to exemplarily stress on the methodological merits and limits of relating phenomenological considerations closer to empirical research. The depressive situation is further specified with an examination of the evaluative dynamics by which individuals meaningfully relate to themselves, others and the world. These evaluative dynamics emerge out of the interplay of pre-reflective and reflective processes, which are significantly altered in depression. Such alterations of the evaluative structure are inextricably intertwined with significant distortions of practical sense in depression. From a phenomenological perspective, these distortions of practical sense show in characteristic experiences of evaluative incoherence and impairments of agency. Finally, this paper focuses on an examination of ‘evaluative incapacity’, which has the integrative potential to capture a range of typical changes of meaningful relatedness that determine the depressive situation.